Recovery of Lithium from Geothermal Fluid at Lumpur Sidoarjo by Adsorption Method - Lukman Noerochim; Gita Akbar Satriawangsa; Amien Widodo (Journal of Engineering and Technological Sciences, 2016)
The recovery of lithium from geothermal fluid at Lumpur Sidoarjo, Indonesia was investigated employing an adsorption method with polymer membrane as container. The lithium concentration in geothermal fluid from Lumpur Sidoarjo used in the present study was about 5 mg/l. Lithium manganese oxide (LMO) was selected as a promising adsorbent material due to its non-toxic, topotactical behavior and low cost. In this study, LMO with single Li/Mn mole ratio was prepared, i.e. Li1.6Mn1.6O4. The adsorbent was synthesized by solid state reaction at 500 °C for 5 hrs. A lithium uptake yield from the geothermal fluid of around 6.6 mg/g was obtained.